Upconversion under Photon Trapping in ZnO/BN Nanoarray: An Ultrahigh Responsivity Solar‐Blind Photodetecting Paper. Issue 22 (15th March 2022) - Liu, Guozhen; Chen, Han; Lu, Shiqiang; Liu, Lian; Xu, Xiangyu; Shi, Lan; Chen, Binghuan; Guo, Bin; Shen, Peng; Cai, Yehang; Zhang, Hongye; Tang, Yan; et al.
Abstract: Solar‐blind photodetectors (PDs) are widely applicable in special, military, medical, environmental, and commercial fields. However, high performance and flexible PD for deep ultraviolet (UV) range is still a challenge. Here, it is demonstrated that an upconversion of photon absorption beyond the energy bandgap is achieved in the ZnO nanoarray/h‐BN heterostructure, which enables the ultrahigh responsivity of a solar‐blind photodetecting paper. The direct growth of ultralong ZnO nanoarray on polycrystalline copper paper induced by h‐BN 2D interlayer is obtained. Meanwhile, strong photon trapping takes place within the ZnO nanoarray forest through the cyclic state transition of surface oxygen ions, resulting in an extremely high absorption efficiency (> 99.5%). A flexible photodetecting paper is fabricated for switchable detections between near UV and deep UV signals by critical external bias. The device shows robust reliability, ultrahigh responsivity up to 700 A W −1 @ 265–276 nm, and high photoconductive gain of ≈2 × 10 3 . A negative differential resistance effect is revealed for driving the rapid transfer of up‐converted electrons between adjacent energy valleys ( Γ to A ) above the critical bias (3.9 V). The discovered rationale and device structure are expected to bring high‐efficiency deep UV detecting and future wearable applications. Abstract : A solar‐blind photodetecting paper based on ZnO nanoarray and 2D h‐BN interlayer is developed with ultrahigh responsivity up to 700 A W −1 @ 265–276 nm and switchable detection bands between UVA (>315 nm) and UVC (<280 nm), through up‐conversion absorption and negative differential resistance effect.